SOCIAL HIERARCHY AND HUMAN INTERACTION IN MOBY-DICK - RAZZAQOVA MADINAXON IQBOLJON QIZI (TADQIQOTLAR, 2026)
Abstract:This article examines the role of social hierarchy, authority, and human interaction aboard the Pequod in Herman Melville’s Moby-Dick. The novel portrays how structured social roles and power dynamics influence individual behavior and collective decision-making. Through Captain Ahab’s authority, Queequeg’s integration into the crew, and the complex interactions among sailors of diverse backgrounds, Melville explores the tensions between hierarchy, cooperation, and conflict. The study argues that the novel highlights the interplay between personal ambition and communal responsibility, demonstrating how social organization shapes human experience in extreme circumstances.